The Great Stranger (Journal of Pedagogical Inventions and Practices, 2024)
The concept of motherland, love for motherland is highlighted in Shavkat Rahman's lyrics. Analysis of Shavkat Rahman's poem “Broken Walls”. The anthem of our hospitable ancestors, the unique mentality of the Uzbek people. A look at the present day from the distant past. Effective and purposeful use of artistic imagery: use of alliteration, anaphora, and contrast. Explanation of the concept of national mentality. Expressing the experiences of the lyrical hero. Respect for ancestral heritage.